Immunological and Molecular Evaluation of IL-5 in Asthma Patients - Baraa Jawad Kadhim; Assist. Prof. Mohammad Reza Khakzad; Assist. Prof. Jenna Khayat Zadeh (Zien Journals, 2023)
Asthma cause airway obstruction and are associated with chronic airway inflammation. Interleukin -5 is mainly produced by Th2 cells, innate lymphoid cells group 2 (ILC2), mast cells, natural killer T cells (NKT), and eosinophils themselves. Material and Method: A case-control study and the implementation steps are divided into 3 main parts, include: Patient selection and sampling, examining the intensity of gene expression. Result: The present study show that the expression of IL-5 gene has increased significantly in asthma. Regarding the intensity of IL-5 gene expression in the patient and control groups, a significant difference can be observed between the two groups in terms of gene expression intensity (PValue=0.0001). Conclusion: The results of the present study show that IL-5 gene expression has been significantly changed in asthma. In terms of the intensity of IL-5 gene expression in the patient and control groups, a significant difference is observed between the two groups (P-Value=0.0001), also the experiment and analysis of the obtained ROC curve shows that a significant change in IL-5 in Asthma.
Keywords: Asthma; Chronic Obstructive Pulmonary Disease; COPD